Early diagnosis of hepatic inflammation in Japanese nonalcoholic fatty liver disease patients using 3D MR elastography. Issue 3 (24th November 2022) - Komiyama, Yasuyuki; Motosugi, Utaroh; Maekawa, Shinya; Osawa, Leona; Nakakuki, Natsuko; Takada, Hitomi; Muraoka, Masaru; Suzuki, Yuichiro; Sato, Mitsuaki; Takano, Shinichi; Fukasawa, Mitsuharu; Yamaguchi, Tatsuya; et al.
Abstract: Background: The damping ratio (DR) and the loss modulus (G″) obtained by 3D MR elastography complex modulus analysis has been reported recently to reflect early intrahepatic inflammation, and is expected to be a noninvasive biomarker of inflammation in nonalcoholic fatty liver disease (NAFLD). However, the role of the DR and the G″ in Japanese NAFLD patients remains unclear. Methods: We enrolled 39 Japanese patients with NAFLD who underwent liver biopsy and 3D MR elastography within 1 month and analyzed the association between DR, G″, and histological activity. Results: Regarding DR, no evident correlation was observed between the DR and histological activity ( p = 0.14) when patients with all fibrosis stages were included. However, when patients were restricted up to stage F2 fibrosis, the association of the DR and inflammation became significant, the DR increasing with the degree of activity ( p = 0.02). Among the constituents of fibrosis activity, ballooning correlated with the DR ( p < 0.01) while lobular inflammation did not. Regarding G″, it was correlated with histological activity ( p < 0.01), ballooning ( p < 0.01), and lobular inflammation ( p < 0.01) in patients with all fibrosis stages and in patients up to F2 fibrosis ( p = 0.03 for activity and p = 0.04 for ballooning). The best cutoff value of DR for hepatitis activity in patients within the F2 stage was 0.094 (area under the receiver operating characteristic curve 0.775, 95% CI: 0.529–1.000) and G″ was 0.402 (area under the receiver operating characteristic curve 0.825, 95% CI: 0.628–1.000). Conclusions: The DR and G″ reflected the histological activity in Japanese patients with NAFLD during the early stage, indicating these values for noninvasive diagnosis of inflammation in Japanese patients with NAFLD.